PERANAN BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT DALAM MENINGKATKAN PELAYANAN KEAMANAN MASYARAKAT DI POLSEK SUMOROTO KABUPATEN PONOROGO - Joko Suranto, Nofta Wulan Sari, Winarti & (Transformasi, 2016)
Research do by researchers aims to understand the role of BHABINKAMTIBMAS Inimproving security services In the precinct Sumoroto Kabupaten Ponorogo. Mean the role ofBHABINKAMTIBMAS in this research was all activity and activities was in line with duty, basicfunction and authority in achieving its objectives organization of BHABINKAMTIBMAS Is toachieve situation KAMTIBMAS ( a security and public order ) steady and dynamic. To knowbenchmark the role of BHABINKAMTIBMAS in the precinct Sumoroto that focuses on increasedservant security can be measured of various indicators. Indicators are: the role ofBHABINKAMTIBMAS as figurehead, the role of BHABINKAMTIBMAS as leader ( leader, therole of BHABINKAMTIBMAS as the officials intermediaries ) liasison manager.In this researchmethods used by researchers is descriptive qualitative. The data collected in this researchcollected by interviews directly then the result is collected and analysed qualitatively to get datadescriptive.After do it data analysis, obtained the result that of various the indicators used ingeneral the results show that the role of BHABINKAMTIBMAS in the precinct SumorotoKabupaten Ponorogo already run its work well and effective. It has been proven the researchthat has been done in the district police stationSumoroto Kabupaten Ponorogo.Keywords: Role; security; services